Biopolitical Devices of Social Integration: The Business of Education for the Poor - Juan Ramón Rodríguez Fernández; Enrique Javier Díez Gutiérrez (Universidad Autónoma de Madrid, 2018)
The minimum income programs are essential public actions in the fight against poverty in the European Union. In this article, we intend to show the characteristics of the minimum income policies for the fight against poverty and the training activities linked to them in the case of Spain. Starting from an analytical strategy based on the approaches of Michel Foucault, we analyze the hegemonic discourses in these minimum income programs: the social-liberal discourse and the neoliberal discourse. For this we use the notions of political rationality and the social symptomatology. Through this discursive analysis we find that, in the actions of struggle against social exclusion, education is configured as an individual investment for the promotion of employability, as an element to claim the individual responsibility of the subject in its own integration process social and as a space susceptible of economic profitability through its configuration as an educational quasi-market. In turn, and this is one of the main results of this work, an emergent hegemonic discourse is identified in the fight against poverty. A discourse resulting from the hybridization of social and neoliberal discourses, which we have called Education as a "neo-crippled saint" against poverty. Keywords: Politics; Speeches; Social justice; Social exclusion; Enterprises.